Inca Gar cilaso, our first gr eat writer - López-Baralt, Mercedes (2017)
This essay examines two masterpieces authored by the Inca Garcilaso de la Vega, The Royal Commentaries and The General History of Peru, pointing to the qualities of his prose that justify his stature as our first Latin American writer. The first part considers symmetry as the guiding principle of his writing, its lyric quality, his appeal as a powerful narrator, his anticipation of the modern genre of autobiography and his creation of unforgettable characters and moving dialogues. The second part approaches Garcilaso's role as mythologist, and explains how his psyquic orphanhood moves him to seek paternal figures and to transform himself into the Andean mythical entity of the wakcha. In his works, the double - an ancestral notion which modernity has coined to explain man's complexity as a conflictive being - becomes the trope that lies behind the creation of his characters, anticipating in more than two centuries the master of the doppelganger, Dostoievski. The essay concludes with a reflection on the relevant presence of the Inca's ethical lesson: the celebration of crossbreeding.